2015
DOI: 10.1589/jpts.27.1121
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chest expansion resistance exercise on chest expansion and maximal respiratory pressure in elderly with inspiratory muscle weakness

Abstract: [Purpose] The aim of this study was to examine the effect of chest expansion resistance exercises (CERE) on chest expansion, maximal inspiratory pressure (MIP), and maximal expiratory pressure (MEP) in elderly people with inspiratory muscle weakness. [Subjects] Thirty elderly people with inspiratory muscle weakness (MIP < 80% of the predicted value) were randomly and equally assigned to a chest expansion resistance exercise (CERE) group, core conditioning exercise (CCE) group, and control group. [Methods] The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
1
15
0
1
Order By: Relevance
“…Based on the experimental results, a significant enhancement in chest expansion was observed at both levels. This finding is consistent with Bezzoli et al (2016), Mongkol (2016), and Kim et al (2015) study results. In the study of Bezzoli et al, in the first session of the motor control exercises, all patients were trained on how to activate the lumbar-pelvic cylinder muscles individually while having an easy diaphragmatic breathing and neutral lumbar posture in supine, sitting, and standing positions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Based on the experimental results, a significant enhancement in chest expansion was observed at both levels. This finding is consistent with Bezzoli et al (2016), Mongkol (2016), and Kim et al (2015) study results. In the study of Bezzoli et al, in the first session of the motor control exercises, all patients were trained on how to activate the lumbar-pelvic cylinder muscles individually while having an easy diaphragmatic breathing and neutral lumbar posture in supine, sitting, and standing positions.…”
Section: Discussionsupporting
confidence: 93%
“…A 200-cm tape measure was used and rib cage circumference at three different levels was measured: 1: The anterior axillary line for Upper Chest Mobility (UCM) (the horizontal line of the spinous process of the fifth thoracic vertebrae and the third intercostal space (axillary line) at the mid-clavicular line); 2: The tip of the xiphoid (the horizontal line of the spinous process of the tenth thoracic vertebrae and tip of the xiphoid process) process for Lower Chest Mobility (LCM) [12]. To standardize all the measurements, the zero point at the tape was first put on the midline of the trunk, horizontally regulated with the markers, and then the other edge of the tape was moved [12]. The difference between maximum inspiration and maximum expiration (each position held his breath for at least 2 seconds) was determined for all three measured circumferences.…”
Section: Chest Wall Mobilitymentioning
confidence: 99%
“…Breathing is movement of air in and out of the lungs in response to volume changes in the thoracic diaphragm, followed by the intercostals, rectus abdominis, TA, and multiple accessory muscles. According to previous research, application of chest expansion resistance exercises by a therapist is recommended if the environment and conditions are appropriate for enhancement of chest expansion capacity and maximal inspiratory pressure in elderly people 19 ) . In the FVC, the TA and intercostals are used to exert pressure on the lower ribs by bending the torso and inducing deep breathing with the lifted diaphragm 20 ) .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Lucyna [7] found that a single application of respiratory stimulation using PNF significantly improved the lung function. Evidence supports effectiveness of CERE to improve stroke patient's walk distance, trunk control, degree of chest expansion, and forced expiratory volume in 1 s (FEV1) [11,17].…”
Section: Introductionmentioning
confidence: 97%
“…Another systematic review on patients with stroke has reported effectiveness of respiratory muscle training in improving respiratory muscle strength [16]. The chest expansion resistance exercise (CERE) is an exercise based on a proprioceptive neuromuscular facilitation (PNF) breathing exercise [17]. A recent study by Lucyna [7] found that a single application of respiratory stimulation using PNF significantly improved the lung function.…”
Section: Introductionmentioning
confidence: 99%